The Sociology of Revolutions - Foran, John (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course will survey the causes, processes, and outcomes of some of the major social revolutions of the modern epoch. Beginning with Theda Skocpol’s path-breaking study of the French, Russian, and Chinese revolutions, we will move to a consideration of revolutions in the Third World (including Cuba 1953-59, Central America in the 1970s and 1980s, and Iran in 1978), then to such democratic revolutions as the French student movement of 1968, Chile under Allende in the 1970s, and the Eastern European revolutions of 1989. We will close by speculating on the future, with special attention to the current crisis in Iraq and the situation unfolding in Chiapas, Mexico.